What is a colon? - du Toit, H. C. (Neotestamentica, 1977)
An attempt is made in the following discussion to provide a definition of a colon. At first, only a preliminary formulation is given to serve as a starting point. We then gradually work up toward a more satisfactory definition in the course of the discussion. In parallel fashion we proceed from a descriptionption of the most elementary colon-structure to more elaborate and complex configurations.